Peer Relationships and Their Impact on Juvenile Delinquency Intensity: A Cross-Sectional Study - Dira, Hayyu; Subardjo, Ratna Yunita Setiyani (The Indonesian Institute of Science and Technology Research, 2025)
Adolescence is a critical developmental stage marked by identity formation and heightened susceptibility to peer influence. This study examined the relationship between peer relationships and juvenile delinquency among 96 adolescents aged 15–21 years, selected through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed with Pearson correlation and simple linear regression. Results indicated that peer relationships significantly influenced juvenile delinquency (p = 0.003, r = -0.301), with higher-quality peer relationships associated with lower levels of delinquent behavior. These findings highlight the importance of school-based interventions and peer mentoring programs to promote supportive peer environments and reduce deviant behaviors among adolescents.